Sexual selection on size and shape in Japanese beetles (Popillia japonica). (20th May 2020) - Kelly, Clint D
Abstract: The mobility hypothesis argues that species in which males compete for mates in scrambles often exhibit female-biased size dimorphism because smaller male body size should increase male mobility and success in searching for mates. Sexual dimorphism can be further exaggerated if fecundity or sexual selection concurrently selects for larger female size. Scramble competition can select for trait characteristics that optimize locomotion; for example, long and slender wings should be favored if aerial speed is important to mating success. I tested these predictions in the scrambling Japanese beetle ( Popillia japonica ), a female-biased size dimorphic insect pest that is invasive to North America. Multivariate selection analyses support the prediction that smaller body size and larger wings in males benefit their mating success. My analyses also revealed significant selection for larger wings in females but, contrary to prediction, direct sexual selection favors smaller body size in females. These results support the mobility hypothesis and partially explain the evolution of female-biased size dimorphism in this species. Sexual selection favored rounder bodies in females and more tapered bodies in males, whereas, in both sexes, the effect of wing shape appears less important to fitness than wing size. Abstract : Japanese beetles with relatively smaller bodies and relatively larger wings have greater mating success than their counterparts. These phenotypes are likely favored by sexual selection because their bearers travel more quickly and arrive on plants earlier than their competitors. By arriving earlier at aggregations, females face less competition for food whereas males guarantee mating opportunities because the sex ratio at aggregations can quickly become male biased.